Pharmacokinetics of flutamide in patients with renal insufficiency - Anjum, S (Blackwell Science Inc, 1999)
AIMS: The aim of this study was to determine the pharmacokinetic parameters of flutamide, a nonsteroidal antiandrogenic compound, and its pharmacologically active metabolite, hydroxyflutamide, in renal insufficiency. Haemodialysis (HD) clearance of flutamide and hydroxyflutamide was also determined. METHODS: Pharmacokinetic parameters were assessed for flutamide and hydroxyflutamide in 26 male subjects with normal renal function (creatinine clearance by 24 h urine collection, CL(cr), greater than 80 ml min(−1) 1.73 m(−2); n = 6) or reduced renal function; CL(cr) = 50–80 (n = 7), 30–49 (n = 3), 5–29 (n = 4), and <5 ml min(−1) 1.73 m(−2)-HD (n = 6), following a single, oral 250 mg flutamide dose. Subjects undergoing HD received a second 250 mg dose of flutamide 4 h prior to HD; blood and dialysate were collected during HD to determine dialysability of flutamide and hydroxyflutamide. RESULTS: C(max), t(max), AUC, t(1/2), and renal clearance of flutamide and hydroxyflutamide did not differ between groups. Less than 1% of the dose appeared in dialysate as hydroxyflutamide. No serious adverse events were observed. CONCLUSIONS: Renal function did not affect flutamide nor hydroxyflutamide disposition. HD did not alter hydroxyflutamide pharmacokinetics. Dosing adjustments for renal impairment or HD are not indicated for flutamide.